Characterization of Agronomic and Quality from Three Clones of Ramie Plant (Boehmeria nivea [L.] Gaud.) in Ultisol Limau Manis - Reni Mayerni (Department of Crop Science, Faculty of Agriculture, Andalas University, 2018)
The quality improvement of ramie, including inner and outer aspects are required to be developed to optimalize its production. Unlike horticulture and food crops, ramie cultivation is not constrained by the soil type. This study was aimed to evaluate the agronomical characteristics of three ramie clones in ultisol land. This study was performed using descriptive analysis method with purposive sampling by collecting 10 clumps per clone. Clones of fiber ramie used were Ramindo 1, Bandung A and Lembang A. All clones were planted in ultisol soil located in 350 m above sea level from September 2015 until March 2016. The highest fiber production was achieved from Ramindo 1 followed by Bandung A and Lembang A. The resulted fiber from all clones was considered as quality class II fiber marked by the nominal value ranging from 400-450. Bandung A exhibited the best quality of fiber with nominal value of 450. In terms of its chemical composition, fiber produced by Lembang A contained the highest cellulose (74.7%) with the lowest lignin content (3.6%).